Quantitative Analysis of tectonic activity in Taftan volcano and around (South East of Iran) - Mohsen Jami; Ali Solgi; محسن پورکرمانی; Aliasgar Moridi (مخاطرات محیط طبیعی, 2016)
Taftan volcano young to age Pliocene-Quaternary and semi-active volcanic system is located 50 kilometers north of the city of Khash. It seems in this area the phenomenon of young volcanoes and tectonically active area morphology have played a major role. According to population centers around the volcano and the earthquake of high magnitude in this area (earthquakes related to Saravan fault), study tectonic activity in this area is important. The Taftan active structures around the importance of this issue twice. The purpose of this study Taftan active tectonic drainage basins, environment and level of tectonic activity in the region is relative. In the field of geomorphic indicators have been used for the study of tectonic activity. These indicators include: the drainage basin asymmetry (Af), mountain front sinuosity (Smf), the slope of the valley (Sl), floor width to valley height (Vf), hypsometric integral (Hi). The index for evaluating relative active tectonic (Iat) basin and sub-basin of the study area were used. A recent survey shows that Neotectonic an important role in the evolution of geomorphic region. Based on the proposed model, recognized three tectonic zones in the study area: (zone with relatively high tectonic activity), this zone is observed only in two sub-basin, 4-B and 9-C, (zone of tectonic activity relative to average) the wide area of the region in this area, it is important that the structures can be noted in the northwest of Dargiaban, Iranshahr fault and fault Saadat-abad, (zone with relatively low tectonic activity) this zone has observations in two sub-basin only 5-C, 1-D, 9A and 8. The results of the analysis of indicators and field observations indicate tectonic activity are also within the scope of Taftan volcano (quantitatively) and its surroundings.